Gadolinium(III)-based porous luminescent metal-organic frameworks for bimodal imaging - Kundu, Tanay; Mitra, Shouvik; Diaz Diaz, David; Banerjee, Rahul (Chempluschem, 2016)
Gd-III-based metal-organic frameworks, Gd-pDBI-1 and Gd-pDBI-2, have been synthesized using the linker pDBI (pDBI=1,4-bis(5-carboxy-1H-benzimidazole-2yl)benzene). They exhibited structural diversity due to subtle change in reaction constituents. Owing to the judicious choice of the fluorescent linker, the materials could be used for bimodal imaging (fluorescent and magnetic resonance) and displayed a modest T1 relaxivity value.

Interplaying anions in a supramolecular metallohydrogel to form metal organic frameworks - Karak, Suvendu; Kumar, Sushil; Bera, Saibal; Diaz Diaz, David; Banerjee, Subhrashis; Vanka, Kumar; Banerjee, Rahul (Chemical Communications, 2017)
The remarkable effect of anions on the transition from supramolecular gels to crystalline phases has been described. An amino acid-based metallohydrogel was transformed into different metal-organic frameworks through the selective picking of anions. The metallohydrogel and the resulting metal-organic frameworks (MOFs) were thoroughly characterized. The results demonstrated controlled access over the binding of a particular anion to selectively form a particular MOF.

Targeted drug delivery in covalent organic nanosheets (CONs) via sequential postsynthetic modification - Mitra, Shouvik; Sasmal, Himadri Sekhar; Kundu, Tanay; Kandambeth, Sharath; Math, Kavya; Diaz Diaz, David; Banerjee, Rahul (Journal of the American Chemical Society, 2017)
Covalent organic nanosheets (CONs) have emerged as a new class of functional two-dimensional (2D) porous organic polymeric materials with a high accessible surface, diverse functionality, and chemical stability. They could become versatile candidates for targeted drug delivery. Despite their many advantages, there are limitations to their use for target specific drug delivery. We anticipated that these drawbacks could be overturned by judicious postsynthetic modification steps to use CONs for targeted drug delivery. The postsynthetic modification would not only produce the desired functionality, it would also help to exfoliate to CONs as well. In order to meet this requirement, we have developed a facile, salt-mediated synthesis of covalent organic frameworks (COFs) in the presence of p-toluenesulfonic acid (PTSA). The COFs were subjected to sequential postsynthetic modifications to yield functionalized targeted CONs for targeted delivery of 5-fluorouracil to breast cancer cells. This postsynthetic modification resulted in simultaneous chemical delamination and functionalization to targeted CONs. Targeted CONs showed sustained release of the drug to the cancer cells through receptor mediated endocytosis, which led to cancer cell death via apoptosis. Considering the easy and facile COF synthesis, functionality based postsynthetic modifications, and chemical delamination to CONs for potential advantageous targeted drug delivery, this process can have a significant impact in biomedical applications.

On the sensitivity of alginate rheology to composition - Suresh, Karthika; Haering, Marleen; Kumaraswamy, Guruswamy; Diaz Diaz, David (Soft Matter, 2019)
The linear response of alginate-phenyl boronic acid (Alg-PBA) esters shows a universal, composition-independent viscoelastic fluid-like behaviour. Reversible association of alginates governs their rheology at all compositions (viz. at all alginate concentrations and solution pH). However, their high strain behaviour is very sensitive to composition. Tuning composition affords liquids that neck to form filaments capable of being drawn to large elongations without failure. We interpret our data by invoking strain-dependent association and dissociation rates for the alginates. High association rates at high strain result in materials with viscoelastic liquid like behaviour.